Evaluation of midwifery students’ satisfaction with regards to clinical internship: Midwifery students’ satisfaction with regards to clinical internship. - Ricchi, Alba; Gemellaro, Giovanna; Menichini, Daniela; Molinazzi, Maria Teresa; Infante, Ramona; Banchelli, Federico; Artioli, Giovanna; Foà, chiara; Neri, Isabella (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. The clinical internship is fundamental for the training of the future socio-health professional. Through the practical activity, the student develops professional skills, critical thinking and decision-making ability, internalizing the complexity of the professional role. While in the nursing field there are several tools for assessing the clinical experience of students, in the obstetric field there is a lack of validated tools. Therefore, the purpose of this work was to investigate the perception of the students of the Degree Course in Midwifery regarding the internship experience. Method. The study was conducted at the obstetric clinical internship where students carry out practical activities and involved all the students of the Degree Course in Midwifery at the University of Modena and Reggio Emilia. The data were collected through an anonymous online questionnaire (Google Model), which was inspired by the nursing CLES + T, simplified and adapted to the obstetric field. Results. In total, 54 students took part in the research (81.8% of all students enrolled in the degree program examined). They were mainly of Italian nationality (98.1%), women (94.4%), aged between 18-22 years (85.2%). In general, the third-year students were more satisfied with the internship experience than the second- and first-year students, most likely for having achieved a degree of autonomy of care, awareness and greater professional motivation. Conclusions. The results indicate the need to periodically investigate the quality and satisfaction of the clinical internships to ensure increasingly effective obstetric training.